Effect of leg dominance on change of direction ability amongst young elite soccer players. Issue 6 (18th March 2016) - Rouissi, Mehdi; Chtara, Moktar; Owen, Adam; Chaalali, Anis; Chaouachi, Anis; Gabbett, Tim; Chamari, Karim
ABSTRACT: Young soccer players often use one particular dominant leg (DL) to perform dynamic movements which require strength, resulting in leg asymmetry. The aim of this study was to compare, in young soccer players, the effect of using DL and non-dominant leg (NDL) on time performance of two change of direction (COD) manoeuvres in several angles of COD. Seventy-three young male soccer players (mean ± SD, age: 16.1 ± 1.8 year) participated in this study. Players performed 10-m sprints, either in a straight line or with a COD (5 m straight ahead and a turn of 45°, 90°, 135° and 180° to the opposite side of the DL or NDL). Testing for COD speed was conducted over two different manoeuvres: (1) sidestepping and (2) bypass. Maximal isometric voluntary contraction of the knee extensors/flexors and hip abductors/adductors was also measured using a handheld dynamometer. For sidestepping, COD performance with use of the DL was significantly better compared to the NDL ( P < 0.05) in all angles of COD. However, bypass COD performance through use of the DL was better compared to the NDL only when turning at 135°. Additionally, strength of the knee extensors/flexors and hip abductors of the DL was significantly ( P < 0.05) greater than the NDL. The use of the DL allows better COD performance than the NDL when sidestepping manoeuvre is used. However, the DL allows better COD performance than the NDL only at 135° with the use of the bypass manoeuvre. Furthermore, the greater strength of the DL compared to the NDL may contribute to COD performance difference between legs.